Improving Economic and Legal Regulation in the Tourism Sector - KOSEVICH, Alexander Valentinovich; NOVIKOVA, Nataliya Gennadievna; GLADKIKH, Victor Ivanovich; SHARONIN, Pavel Nikolaevich; SMIRNOV, Mihail Alexandrovich (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020, 2020)
The article deals with the improvement of economic and legal regulation in the tourist sector. To solve the regulation issues of the tourism sector, it is proposed to use a multidisciplinary approach, whose essence is trying to integrate a variety of scientific areas and concentrate them in the tourism sector. It is proved that the application of this approach in the analysis of economic and legal regulation of tourism activities will allow considering more fully and systematically the regulation of relations in the tourism sector, identifying their patterns, and suggesting ways to develop the tourism industry in the current context. It is revealed that the main expected results of the tourism policy are growing the tourist flow and increasing the development level of the tourism industry. At that, the target indicators of the tourism policy are the number of accommodation facilities and the number of people working in tourist companies.